Preliminary Evaluation of Dietary Natustat™ Versus Histostat® (Nitarsone) for Control of Histomonas meleagridis in Broiler Chickens on Infected Litter - Duffy, C.F.; Sims, M.D.; Power, R.F. (International Journal of Poultry Science, 2004)
Histomoniasis (infectious enterohepatitis) is a disease of broiler chickens, turkeys and game fowl which are reared on litter or exposed to range. It is caused by the protozoan organism Histomonas meleagridis. Histomonads are spread in chicken feces, Heterakis gallinarum (cecal worm) eggs or earthworms. Symptoms may include: poor feed conversion ratio and body weight, diarrhea with sulfur-colored droppings, cecal and liver lesions, darkening of the facial regions and sometimes death. Morbidity, mortality and culling may reach 20% in chickens. In the U.S.A., nitarsone (4-nitrophenyl-arsonic acid; Histostat®, Alpharma, Inc., Fort Lee, NJ) is used as an aid in prevention of histomoniasis. In this trial, Natustat™ (Alltech, Inc., Nicholasville, KY), a proprietary plant derived product, was used at 1.925 kg/Tonne and compared with nitarsone in the diets of unsexed Hubbard HiY broiler chicks to 42 d of age on histomonad infected litter from broiler breeders. Infected and uninfected control groups were also included. There were 4 pens each containing 150 chicks (unreplicated live performance) and 25 birds per pen were randomly sampled at 28, 35 and 42 d of age for cecal (0-4) and liver lesion (0-3) scoring. The histomonad infected litter group had significantly elevated cecal and liver lesion scores compared to the uninfected control group, indicating the challenge model was effective. At each sampling point, Natustat™ was statistically equivalent to nitarsone for lowering cecal or liver lesion scores and these treatments gave results significantly better than infected control.